Water-deficit effects on alfalfa at various growth stages - Abd Halim, Mohd Ridzwan; Buxton, D. R.; Hattendorf, Mary J.; Carlson, R. E. (American Society of Agronomy, 1989)
Studies of water-deficit effects on forage quality of alfalfa (Medicago sativa L.) have generally considered water stress throughout plant growth. This experiment was conducted to compare, with an unstressed control, the effects of short-term soil-water deficits occurring at three growth stages. Plants were grown in 100-L containers set into the ground and protected with an automatic rain-out shelter. Control treatments were watered weekly or twice weekly to raise the soil-water level to field capacity. Watering was excluded during the third or fourth week of regrowth for plants that were stressed at vegetative and bud stages, respectively. For plants stressed at the flower stage, watering was excluded during the sixth or seventh week. Plants were harvested at five weekly intervals beginning 21 d after an initial defoliation. Stress at the bud or flower stages reduced leaf-to-stem ratio (LSR) by 25 and 38% of control, respectively. Stress at the vegetative stage did not affect LSR. As a result of lower LSR, in vitro digestible dry matter (IVDDM) in plants stressed at the bud or flower stages was 4% less than that of the control. The IVDDM of herbage in plants stressed at the vegetative stage was not different from the control. Crude protein (CP) concentration in stems increased by up to 8% of the control when plants were stressed at the vegetative or bud stages. Concentration of CP in leaves of stressed plants was 5 to 11% less than that of the control. Herbage CP concentration was up to 12% less than that of the control with stress at the bud or flower stages. Cell wall (CW) concentration in stems and total herbage was generally lower in plants stressed at the vegetative and bud stages. After rewatering, forage quality recovered in plants stressed at the bud stage. Most of the decline in forage quality due to stress at the bud or flower stages was caused by reduction in LSR and deterioration of leaf quality